The Implementation of the Strategy of Association Increases Students’ Participation in the English Class (2022)
Teachers are in constant search of new techniques and strategies to implement in their classroom; in order to generate students’ engagement or improve their lessons. This research study takes into account the strategy of association as a tool to increase students’ participation in the English class. It is fundamental to know that this proposal explores two types of associations. Association with pictures and association with a topic. Following this logic, this study was made as a qualitative research in order to understand how students are affected by everything that surrounds them before and after the implementation of this strategy.